The differential impact of friendship on cooperative and competitive coordination - Gabriele Chierchia; Fabio Tufano; Giorgio Coricelli (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2020)
Friendship is commonly assumed to reduce strategic uncertainty and enhance tacit coordination. However, this assumption has never been tested across two opposite poles of coordination involving either strategic complementarity or substitutability. We had participants interact with friends or strangers in two classic coordination games: the stag hunt game, which exhibits strategic complementarity and may foster "cooperation", and the entry game, which exhibits strategic substitutability and may foster "competition". Both games capture a frequent trade-off between a potentially high paying but uncertain option and a low paying but safe alternative.We find that, relative to strangers, friends are more likely to choose options involving uncertainty in stag hunt games but the opposite is true in entry games. Furthermore, in stag hunt games, friends "tremble" less between options, coordinate better and earn more, but these advantages are largely decreased or lost in entry games. We further investigate how these effects are modulated by risk attitudes, friendship qualities and interpersonal similarities.
Keywords: C72; C92; D80; 330; coordination; entry game; friendship; strategic complementarity; strategic substitutability; stag hunt game; strategic uncertainty